Evaluating calcipotriene 0.005% foam for the treatment of plaque psoriasis of the scalp and body in patients aged 12 years and older. (24th March 2021) - Gao, Jia C.; Emmerich, Veronica K.; Feldman, Steven; Strowd, Lindsay C.
ABSTRACT: Introduction : Topical corticosteroids are the mainstay of treatment for mild-to-moderate psoriasis in adult and adolescent patients but there can be many adverse events associated with long-term corticosteroid use. Corticosteroid-sparing alternatives include Vitamin D3 analogs, such as calcipotriene (also known as calcipotriol), which have long been used as monotherapy or combination therapy with other topical agents to treat psoriasis. Calcipotriene's mechanism of action is not fully understood but it is believed to be effective due to its anti-proliferative and anti-inflammatory properties. Areas covered : Herein, the authors review the safety and efficacy of calcipotriene 0.005% aerosol foam, as well as factors affecting patient adherence to topical therapies. The authors offer an expert opinion and future perspectives on the use of calcipotriene foam as monotherapy compared with other topical pharmacotherapies. Expert opinion : Calcipotriene 0.005% foam is a safe and effective topical treatment when used to treat plaque psoriasis in patients aged 12 years and older. Despite its safety and efficacy, it remains largely utilized as a second-line agent due to its slow clinical improvement. Slow onset of action can result in poor patient adherence.